Eksistensi Wanita Yang Terefleksi Dalam Novel “Cantik” Karya Vanny Chrisma W (Kajian Feminisme Sastra) - Elfina; Zahra, Rita; Zulkifli; Nurhayati (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2024)
This study aims to describe the existence of women reflected in the beautiful novel by Vanny Chrisma W. The approach used in this study is a qualitative approach, the type of research is a feminist study. The data in this study are words and sentences in the Beautiful novel by Vanny Chrisma W. Data collection was carried out using library study techniques. Data analysis techniques were carried out qualitatively. The results of the study indicate that the existence of women in the novel is an existence in the fields of education and social. While the existence in the fields of law, economics and politics is not found in the novel